The Activation Mechanisms of Co-Housing Design - kameelah Ahmed Al-qaissi; Rana Mazin Mahdi (Iraqi Journal of Architecture and Planning, 2017)
The interesting in organizing residential complex is the most important challenges facing the process of social, economic and environmental development issues, therefore, the work on solving design, planning and organizational problems is one of the most important issues currently under discussion, in view of the fact that the population should not only be targets for development but real participants, and not to isolate community participation, waiting for the right moment for its development, or to put it in its proper framework. This study deals with community participation in housing design from the conceptual and applied aspects and analysis of the interaction between the community and the different degrees of participation. The analysis included studies dealing with participatory design for avariety of purposes, to build a knowledge base and to develop mechanisms that can be used whenundertaking housing projects, the general approch of the research is to study the concept ofparticipatory design in the cognitive aspects and explore its privacy in the buildings of residentialcomplexes, the research problem identified as a knowledge gap about the concept of participatorydesign in the design and planning of residential complexes, the research assumes that the level of usreself-selection determines the participatory space pattern and the mechanism used in the co-design, theresearch found that there is a multiplicity of concepts of co-housing design and therefore multiplemechanisms of dealing with residential participatory space. It is sometimes takeing the concept of(Collarborative Housing); its mechanism of residential participatory space design is (mixed uses)space to create interaction and partnership between the residents of the complex. And sometimes theconcept of (Collective Housing), (which adopts the space saving mechanism for some semi-privateresidential activities such as food places, living space, children's play space, etc., will be removed fromthe apartments to be shared with residents of the complex as public spaces participatory, in return forthe provision of other residential spaces (Save and Share)). The level of high user self-selection at thedesign stage has determined the preference collarborative space pattren in residential complexes withinthe local environment.